If the shoe fits the Windsor Smith marketing and communication case study - McAuliffe, Marc; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2002)
This program focuses on the four key elements that make up Windsor Smith's marketing mix and are often described as the'four Ps': product, price, place and promotion. Looks at each of these areas in relation to the high profile marketing campaigns conducted by the company and also makes reference to marketing objectives, market research, the target market and marketing channels
Title from title screen
DVD format
Keywords: Windsor Smith (Firm); Communication in marketing -- Case studies; Footwear industry -- Australia; Marketing -- Australia -- Case studies